2022
DOI: 10.1097/md.0000000000029566
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of multimodality remote monitoring of maternal physiology during pregnancy

Abstract: Gestational hypertension affects 10% of pregnancies, may occur without warning, and has wide-ranging effects on maternal, fetal, and infant health. Antenatal care largely relies on in-person appointments; hence, only <4% of the pregnancy period is subject to routine clinical monitoring. Home monitoring offers a unique opportunity to collect granular data and identify trends in maternal physiology that could predict pregnancy compromise. Our objective was to investigate the feasibility of remote multidomain mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The widespread acceptance of SHMTs among expectant parents [ 34 ], coupled with the fact that their use is considered extremely feasible by them [ 35 ], as well as the empirical evidence suggesting that their use can have a positive impact on the health of pregnant persons [ 36 ] and can reduce their stress levels [ 37 ], should not obscure the fact that their use also brings some disadvantages. In addition to privacy and data protection issues [ 38 , 39 ], the use of SHMTs can also produce new health-related uncertainties.…”
Section: New Uncertainties Produced By the Use Of Smart Health Monito...mentioning
confidence: 99%
“…The widespread acceptance of SHMTs among expectant parents [ 34 ], coupled with the fact that their use is considered extremely feasible by them [ 35 ], as well as the empirical evidence suggesting that their use can have a positive impact on the health of pregnant persons [ 36 ] and can reduce their stress levels [ 37 ], should not obscure the fact that their use also brings some disadvantages. In addition to privacy and data protection issues [ 38 , 39 ], the use of SHMTs can also produce new health-related uncertainties.…”
Section: New Uncertainties Produced By the Use Of Smart Health Monito...mentioning
confidence: 99%
“…Christoph Lees et al [10] conducted a study to discover the feasibility of remote vital monitoring for pregnant women. In their study they observed 24 women in the regular interval of their first trimester to postpartum.…”
Section: A Related Workmentioning
confidence: 99%
“…The issue of frequency of blood pressure measurements is an important one. A study prior to this conducted by our group, Zielinska et al [2] demonstrated that when women were asked to take daily BP measurements, four per week were obtained on average. Hence, based on this, we did not believe it was feasible to request multiple measurements throughout the day using standard blood pressure monitors.…”
mentioning
confidence: 99%